1989
DOI: 10.1097/00000658-198909000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Revascularization Rather than Cardiac Transplantation for Chronic Ischemic Cardiomyopathy

Abstract: Patients with very poor ventricular function have been thought to be highly vulnerable to elective myocardial revascularization. Ischemic cardiomyopathy is now the major indication for cardiac transplantation. The 2-year survival of medically treated patients with ejection fractions less than 20%, but who are not sufficiently symptomatic for cardiac transplantation, is less than 25%. At our institution we have taken an aggressive approach by using myocardial revascularization for chronic ischemic cardiomyopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…Coronary revascularization may be beneficial for patients with ischemic cardiomyopathy; however, there are significant perioperative risks (1)(2)(3). 18 F-FDG PET has been shown to be the most sensitive noninvasive means for the prediction of left ventricular functional recovery after coronary revascularization (4).…”
mentioning
confidence: 99%
“…Coronary revascularization may be beneficial for patients with ischemic cardiomyopathy; however, there are significant perioperative risks (1)(2)(3). 18 F-FDG PET has been shown to be the most sensitive noninvasive means for the prediction of left ventricular functional recovery after coronary revascularization (4).…”
mentioning
confidence: 99%
“…We have shown in the past that patients with ischemic cardiomyopathy can undergo coronary artery bypass or mitral valve replacement safely. 2,3 Heart transplantation has evolved as the treatment for ischemic cardiomyopathy refractory to the above surgical strategy 4 but donor shortage and cost are the major issues. Several new ventricular remodeling procedures have been proposed for the treatment of the dilated ventricle secondary to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Limitations of the Study Data acquisition during dobutamine was performed with one dose of 10 µkg/kg/min. It was impossible to increase the dobutamine dose gradually on-line for wall motion assessment with each dose, as for echocardiography.…”
Section: Prediction Of Improvement In Left Ventricular Ejection Fractionmentioning
confidence: 99%
“…[1][2][3] A pooled analysis of 37 studies by Bax et al 4 showed that perfusion imaging (by thallium and sestamibi), 18 F-fluorodeoxyglucose ( 18 FDG) metabolic imaging with positron emission tomography (PET), and dobutamine echocardiography are useful techniques for assessing myocardial viability, with a high sensitivity in predicting wall motion improvement, in patients after revascularization. [4][5][6][7][8][9][10][11][12][13] However, the specificity of the perfusion agents, especially thallium, is low.…”
Section: Introductionmentioning
confidence: 99%